Dance Like a Flamingo - Moira Butterfield; Moira Butterfield (london Welbeck edition, 2020)
This is a children$1 (Bs picture/activity book designed to be fun, interactive, and educational for young readers (about age 3 and up). It introduces a variety of animals from around the world and shows how each one moves, encouraging kids to imitate those movements and (3z(Bdance like(3y (Bthe animals. Each spread features a different creature and includes playful, step-by-step actions so children can scuttle, leap, waggle, hop, wriggle, and jump just like the animals they$1 (Bre learning about. The book is colourful, lively, and ideal for read-aloud sessions or engaging group activities that combine learning about wildlife with physical play.s